Implementation of a holonic control system in a flexible manufacturing system - Leitão, Paulo (2009)
Answering to the need to have innovative manufacturing control systems tailored to the current economical, technological, and customer trends, where dynamic and volatile environments prevail, adaptive holonic control architecture (ADACOR) aims to increase the agility and reconfigurability of the production system, contributing for the improvement of the enterprise competitiveness when it works in dynamic and volatile environments. The paper describes the implementation and experimental validation of an ADACOR-based holonic manufacturing control system in a real flexible manufacturing system, using multiagent systems technology. The results extracted from a set of experimental tests allowed to verify the correctness, applicability, and merits of the ADACOR concepts and also contribute to prove the applicability of multiagent systems in industrial environments.